Mubadalah : Metode Interpretasi Adil Jender Bagi Hakim Pengadilan Agama Dalam Memutus Sengekata Hukum Keluarga - Nafi, Muhammad; Mohammad Sahli Ali (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This article aim to description about mubadalah interpretation can be an alternative solution for judges in an effort to present a verdict in a gender-just Islamic family law dispute. Mubadalah interpretation is the interaction between text and reality, which is expected to give constructive meaning to the fact of life and raise the principles of relations between men and women. The findings of this research is there are three steps that the judge can take in interpreting the mubadalah, namely finding the principal value, then looking for the main idea or moral suitable, and finally lowering the moral ideal to the type of calamine that is not mentioned in the text.